An encyclopedic review on stereotactic hypofrac tionated radiotherapy, re-irradiation, and cancer genome research - Heidari, Alireza; Peterson, Victoria (International Journal of Advanced Chemistry, 2020)
Cancer is a disease that humans have been involved with, and scientists have done great efforts to treat it. But they have not had much success, On the other hand Nano science as a new scientific in various branches of science have been made many changes. Hence can be used to treat cancer of Nano science. Currently, cancer treatment is such that drugs used are not selectivity. The cancer cells are not specifically identified, it destroys healthy tissue and cause harm to the human body. So if we can reduce drug dose of the drug to the targeted tissue must be, we have partially solved the problem. With earlier studies, researchers in the field of folate and gold nanoclusters have done, specified in the detection and destruction of cancer cells are highly effective and very promising future. The gold nanoclusters were used because it has unique properties such as adsorption of heat for the destruction of cancer cells and is also well connected to the folate. the 4-aminothiophenol (4Atp) is one of the best linker for binding folate and gold Nano clusters. In this study we used computational method for computing stability of complex (folate and Nano clusters) and geometrical and physicochemical properties.Â